Design of Single Lead Electrocardiography using Filter Order 3 to Reduce Noise Using Spektrum Analysis Based on Fast Fourier Transform - Anita Miftahul Maghfiroh; Singgih Yudha Setiawan; Levana Forra Wakidi (International Journal of Advanced Health Science and Technology, 2023)
Electrocardiography (EKG) is a method commonly used to measure the performance of the human heart through the heart's electrical activity. To obtain the ECG signal, a lead is carried out using electrodes attached to the skin surface which are recorded in the frequency range 0.05-150Hz. The characteristics of the ECG signal consist of the PR interval, QRS complex and QT interval, from these waveforms doctors can diagnose a disease. However, to get a quality ECG signal, there are often disturbances, such as interference with the 50Hz frequency from electrical grids, respiratory movements, or it could also be caused by the ECG processing algorithm, so it is feared that an error will occur in the diagnosis. From these problems, an appropriate ECG filter is needed to reduce the error rate in generating a wave and maintain signal quality so that it can be accepted clinically. This study aims to design an ECG using a 3rd order filter. The ECG input signal is amplified by an instrument amplifier with 100-fold gain, then a filter process is carried out using a 3rd order Low pass filter to reduce noise interference and then a notch filter is used to ward off the 50Hz network frequency. The results of making a 3rd order filter are able to reduce noise and be able to detect ECG signals properly. It is hoped that this research can be used as a reference for filter design for EKG production and can be utilized in clinical use.